Muridae (Mammalia, Rodentia) de los sondeos de Zuurland cerca de Rotterdam (Holanda) - Reumer, Jelle W.F. (Coloquios de Paleontología, 2003)
The true mice (Muridae) from the Zuurland boreholes are described. Four species have been identified. The most common taxon is Apodemus sylvaticus, present in the 42-93 m levels, while one specimen of A. flavicollis was found in the Holocene 20-21 m levels. Representatives of the genus Micromys are found in the 91-92 m levels (M. cf. M. praeminutus) and the 14-66 m levels (Micromys minutus). The biostratigraphical and paleoecological implications of the finds are discussed. An ecological and thus stratigraphical differentiation is suggested within the interval of 42 to 66 m depth, with Eburonian or Early Waalian age in the upper part, and Late Tiglian age in the lower part of this interval.
Keywords: Pleistocene; Holocene; Rodentia; Muridae; Apodemus; Micromys; Taxonomy